EXTREMELY PECULIAR STARS - Pavlenko, Yakiv V. (Одеські астрономічні публікації, 2007)
The procedure and results of modelling atmospheres, spectral energy distributions and spectra of peculiar stars are discussed. A special attention is drawn to the consideration of the particular problems encountered for peculiar and hydrogen defficient stars on the later stages of evolution. We present some results obtained by fits to observed optical and IR spectra of Sakurai’s object, V838 Mon, and RS Oph.